2011
DOI: 10.1177/0047287511418371
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Country-of-Origin Effects of Product Perceptions on Destination Image

Abstract: Via two experiments, the authors meld research in travel destination image (TDI) and country-of-origin image (COI) to investigate whether consumers’ perceptions of a country’s products influence their perceptions of the country as a travel destination. In the first experiment, the authors show that reverse COI effects may occur, where participants use product beliefs to imbue destination beliefs. More positive product beliefs lead to more favorable perceptions of and greater intentions to tour the destination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 50 publications
1
77
0
4
Order By: Relevance
“…Baloglu [30] found that the higher the familiarity with a destination, the more positive the perceptions of it, both in the cognitive and affective dimensions. Another study a decade later echoed that finding, showing that higher familiarity correlated with more positive destination images [35]. Familiarity may moderate the relative influence of different kinds of antecedents on attitudes or images and on the influence of both image and attitude on a tourist's behavior [36].…”
Section: The Moderating Effect Of Familiaritymentioning
confidence: 99%
“…Baloglu [30] found that the higher the familiarity with a destination, the more positive the perceptions of it, both in the cognitive and affective dimensions. Another study a decade later echoed that finding, showing that higher familiarity correlated with more positive destination images [35]. Familiarity may moderate the relative influence of different kinds of antecedents on attitudes or images and on the influence of both image and attitude on a tourist's behavior [36].…”
Section: The Moderating Effect Of Familiaritymentioning
confidence: 99%
“…Destination image continues as a major area of study (Lee & Lockshin, 2012;Li & Stepchenkova, 2012) in perceptions-related tourism CB research. Similarly, perceived service quality remains another topical area of research in tourism where perceptions are of importance.…”
Section: Perceptionsmentioning
confidence: 99%
“…In fact, a desire to combine the two fields together has recently been exhibited (Lee & Lockshin, 2012;Zhou & Zhou, 2013). For example, Elliot's (2008) study conceptualized the relationships among PCI and TDI constructs and measured empirically their relationships.…”
Section: Introduction and Purposementioning
confidence: 99%